Comparison of Different Restoration Techniques for Endodontically Treated Teeth - Lukarcanin, Jusuf; Sadıkoğlu, İsmail Serhat; Yaşa, Bilal; Türkün, Lezize Şebnem; Türkün, Murat (International Journal of Biomaterials, 2022)
The aim of the present study is to evaluate the physical properties of endodontically treated teeth restored with five different restorative techniques and materials. Hundred and forty extracted human molar teeth were used. In addition to five restoration groups, specimens with no restorations were used as the negative control, and intact molar teeth were used as the positive control. For flexural strength tests, material specimens were made from 5 different materials using a mould according to ISO 4049 standards. One-way ANOVA revealed that the fracture resistance was significantly affected by the restoration type. SFRC group showed the best fracture resistance values, while lowest values were seen in the GWF group. The test results of flexural strength showed values between 140 and 184 MPa and modulus of elasticity between 6.33 and 18.89 GPa (p<0.05). Under the limits of this study, results showed that SFRC can be used to increase the fracture resistance of ETT.